Impact of Water, Sanitation and Hygiene Poverty on Child Health in Pakistan: Evidence from Micro Data - Qurat-ul-Ann, Abre-Rehmat; Rizvi, Syed Badar-ul-Husnain; Bibi, Maryam (Pakistan Journal of Humanities and Social Sciences, 2023)
Attainment of SDGs by Pakistan and emphasis on hygiene and sanitation during and after COVID-19 pandemic signifies importance of current study which analyzes the effect of conditions of water, sanitation and hygiene facilities at household level on child health. This study uses household data from PSLM Survey 2018-2019. Results of zero-inflated poisson regression reveal that a one-unit increase in household water poverty significantly increases expected log outcome of the number of children with diarrhoea. One-unit increase in sanitation poverty increases expected log of number of children with diarrhoea significantly by 1.462. A one-unit increase in household multidimensional hygiene poverty of the household insignificantly increases the expected log of number of children under age five with diarrhea. Rural households have more children affected from diarrhea when household is multidimensional water, sanitation and hygiene poor compared to urban households. There is a significantly high impact on child health in Balochistan and Sindh if water, sanitation, and hygiene poverty increases by one unit with households in KP as reference group. Household characteristics like type of wall, floor, and roof significantly determine the expected change in the log number of children suffering from diarrhea in a water-poor, sanitation poor and hygiene poor household in Pakistan. The study recommends targeted and stern policy formulation along with the effective implementation of existing policies to attain the associated sustainable development goals.